International Society of Psychiatric Genetics Ethics Committee: Issues facing us. Issue 8 (23rd May 2019) - Lázaro‐Muñoz, Gabriel; Sabatello, Maya; Huckins, Laura; Peay, Holly; Degenhardt, Franziska; Meiser, Bettina; Lencz, Todd; Soda, Takahiro; Docherty, Anna; Crepaz‐Keay, David; Austin, Jehannine; Peterson, Roseann E.; et al.
Abstract: Psychiatric genetics research is improving our understanding of the biological underpinnings of neurodiversity and mental illness. Using psychiatric genetics in ways that maximize benefits and minimize harms to individuals and society depends largely on how the ethical, legal, and social implications (ELSI) of psychiatric genetics are managed. The International Society of Psychiatric Genetics (ISPG) is the largest international organization dedicated to psychiatric genetics. Given its history, membership, and international reach, we believe the ISPG is well‐equipped to contribute to the resolution of these ELSI challenges. As such, we recently created the ISPG Ethics Committee, an interdisciplinary group comprised of psychiatric genetics researchers, clinical geneticists, genetic counselors, mental health professionals, patients, patient advocates, bioethicists, and lawyers. This article highlights key ELSI challenges identified by the ISPG Ethics Committee to be of paramount importance for the ethical translation of psychiatric research into society in three contexts: research settings, clinical settings, and legal proceedings. For each of these arenas, we identify and discuss pressing psychiatric genetics ELSI dilemmas that merit attention and require action. The goal is to increase awareness about psychiatric genetics ELSI issues and encourage dialogue and action among stakeholders.